Optical Reflection-Intensity-Distribution Reproduction Based on the Detection of Interference Spectrum Distribution -A Phase Sensitive Interference Component Detection Method - ANDOU, Naoki; ICHIMURA, Tsutomu; TAN-NO, Naohiro; FUNABA, Tadayuki; ENDOU, Sigeru (Rēzā kenkyū, 1996)
We propose and confirm a novel optical frequency domain reflectometry based on the phase sensitive detection of an interference specrum by using a multi-mode laser as a source. The main advantage of this method is its high sensitivity because of the phase sensitive detection of only an interference spectrum signal component. As a result, the dynamic range of the measurement can be improved. The experimental data show that this method is more sensitive than direct detection methods of interference spectra.